GIS tutorial for crime analysis - Gorr, Wilpen L.; Kurland, Kristen S. (Redlands, Calif. : ESRI Press : Distributed to the trade in No rth America by Ingram Publisher Services, 2012)
A computer workbook to teach crime mapping and analysis skills using ArcGIS Desktop software. Includes a 180-day trial version of ArcGIS De sktop 10 software and exercise data.
1. Working with crime maps -- Introduction to crime mapping and anal ysis -- Exploring ArcGIS desktop -- Using crime maps -- Designing and b uilding crime maps -- 2. Conducting crime analysis -- Querying crime ma ps -- Building crime map animations -- Conducting hot spot analysis -- 3. Building a crime mapping and analysis system -- Assembling jurisdict ion maps -- Preparing incident data for mapping -- Automating crime map s.
Includes bibliographical references.
Keywords: ArcGIS; Crime analysis -- Data processing; Geographic information systems; Digital mapping